Glucose‐6‐phosphate‐dehydrogenase deficient red blood cell units are associated with decreased posttransfusion red blood cell survival in children with sickle cell disease. Issue 5 (14th February 2018) - Sagiv, Eyal; Fasano, Ross M.; Luban, Naomi L. C.; Josephson, Cassandra D.; Stowell, Sean R.; Roback, John D.; Francis, Richard O.; Yee, Marianne E. M.
Abstract: Chronic transfusion therapy (CTT) for sickle cell disease (SCD) reduces disease morbidity by suppressing the amount of circulating hemoglobin S (HbS)‐containing red blood cells (RBC). The effectiveness of CTT depends on the rate of RBC clearance. Glucose‐6‐phosphate dehydrogenase (G6PD) deficient donor RBC may exhibit increased hemolysis, but it is unknown if transfusion of these units results in less effective transfusion outcomes in SCD. Children with SCD on CTT were followed prospectively for multiple transfusions. G6PD activity of transfused units was measured prior to expiration date. HbA clearance (ΔHbA) was calculated as the difference of estimated posttransfusion HbA to the pretransfusion HbA of the subsequent transfusion episode. Sixty‐two patients received 388 transfusions. Of 755 RBC units, 687 (91%) had normal G6PD (>60% activity), 38 (5%) had moderately low G6PD (10‐60% activity), and 30 (4%) had severely low G6PD (<10% activity). Of 358 evaluable transfusions, 54 (15%) included ≥1 G6PD deficient units, and 22 (6%) had ≥1 severely deficient units. The proportion of the transfusion episode consisting of G6PD deficient units was associated with increased ΔHbA for all G6PD deficient units ( P  = .05) and for severely G6PD deficient units ( P  = .0070). In multivariate mixed effects modeling, ΔHbA was positively associated with severely G6PD deficient units ( P  = .0074) and RBC alloimmunization ( P  = .03) and negatively associated with recipient splenectomy ( P  = .015). Higher ΔHbA was associated with higher HbS and reticulocyte counts at the subsequent transfusion episode. In conclusion, G6PD deficient RBC transfusions may have shorter in vivo survival and adversely affect the suppression of sickle erythropoiesis.